Multiethnic Malaysia past, present, and future - Lim, Teck Ghee; Gomes, Alberto G. 1954-; Rahman, Azly; Malaysian Institute of Development and Asian Studies; Strategic Info Research Development (Selangor, Malaysia Strategic Information and Research Development Centre and MiDAS@UCSI University, 2009)
A survey of the interaction of race, ethnicity, nationalism and politics in Malaysia. It examines the historical roots of national and ethnic identity, the sources of conflict and social cohesion, and contemporary manifestations of ethnic tension and solidarity in areas such as economic policy, cultural politics, education and migration. In doing so, the contributors delineate a variety of possible paths to reconciliation and the construction of a genuinely multiethnic society.--From publisher description.
Pt. 1. Historical roots of identity in Malaysia -- pt. 2. Politics, economics, culture and identity -- pt. 3. Education, culture and identity -- pt. 4. Marginalised communities, marginalised identities -- pt. 5. Future prospects.
Includes bibliographical references and index.
Keywords: Cultural pluralism -- Malaysia; Malaysians -- Ethnic identity; Malaysia -- Ethnic relations; Malaysia -- Social conditions